Urban and regional planning - Hall, Peter (Routledge, 2011)
Includes bibliographical references and index; Planning, planners and plans -- The origins: urban growth from 1800 to 1940 -- The seers: pioneer thinkers in urban planning, from 1880 to 1945 -- The creation of the postwar planning machine, from 1940 to 1952 -- National/regional planning from 1945 to 2010 -- Planning for cities and city regions from 1945 to 2010 -- Planning in western Europe since 1945 -- Planning in the United States since 1945 -- The planning process